Classroom versus individual working memory assessment: predicting academic achievement and the role of attention and response inhibition. Issue 1 (2nd January 2020) - Friso-van den Bos, Ilona; van de Weijer-Bergsma, Eva
ABSTRACT: Working memory (WM) is an important predictor for academic learning and achievement. Typically, children's WM is assessed in controlled testing situations, which might not reflect functioning in typical classroom learning situations with natural distractions. In this study, we compared WM performance in controlled and classroom situations and their predictive value for academic achievement. Also, we examined whether performance differences between situations were moderated by attention or response inhibition. In a within-subjects design, primary school children completed visuospatial and verbal WM tasks in two settings (classroom versus controlled individual setting). First, WM functioning was lower in the classroom setting. Second, attention moderated individual differences in this discrepancy between settings, but response inhibition did not. Third, classroom obtained verbal WM scores were the strongest predictors of academic achievement. Our results indicate that classroom assessment of verbal WM provides a more ecologically valid measurement of WM abilities in a real-life learning situation.